2018
DOI: 10.3389/fnins.2018.00748
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Related Brain Activation Is Altered in Older Adults With White Matter Hyperintensities Using Multi-Echo fMRI

Abstract: Cognitive decline is often undetectable in the early stages of accelerated vascular aging. Attentional processes are particularly affected in older adults with white matter hyperintensities (WMH), although specific neurovascular mechanisms have not been elucidated. We aimed to identify differences in attention-related neurofunctional activation and behavior between adults with and without WMH. Older adults with moderate to severe WMH (n = 18, mean age = 70 years), age-matched adults (n = 28, mean age = 72), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 98 publications
3
19
0
1
Order By: Relevance
“…In our study, the LA patients demonstrated decreased functional connectivity between the DMN and the right FIC in SN, especially in the bilateral PCC and vmPFC, consistent with previous studies (Menon and Uddin, 2010; Li et al, 2015; Reijmer et al, 2015; Atwi et al, 2018; Wang et al, 2019). It may indicate that LA leads to the decrease of FC between the SN and DMN, and the damage of connectivity between the DMN and SN.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the LA patients demonstrated decreased functional connectivity between the DMN and the right FIC in SN, especially in the bilateral PCC and vmPFC, consistent with previous studies (Menon and Uddin, 2010; Li et al, 2015; Reijmer et al, 2015; Atwi et al, 2018; Wang et al, 2019). It may indicate that LA leads to the decrease of FC between the SN and DMN, and the damage of connectivity between the DMN and SN.…”
Section: Discussionsupporting
confidence: 92%
“…We had sufficient statistical power to detect small-to medium-sized effects, but we found that the influence of response-incompatible distractors did not vary significantly with adult age. Previous research with the Stroop task (Augustinova et al, 2018;Spieler et al, 1996) and other forms of choice RT (Machado et al, 2009;Maylor & Lavie, 1998) have reported an age-related increase in vulnerability to the effect of response incompatibility, but age constancies have also been obtained (Atwi et al, 2018;Hsieh & Lin, 2014;Kramer et al, 1994;Madden & Langley, 2003). One possibility is that, in the context of the minimal attentional demands of feature search, age-related deficits in performance are more clearly evident when the task challenges the more sensory-level initial stages of feature registration than later, response-dependent stages (Madden et al, 2014;Monge & Madden, 2016).…”
Section: Search Performancementioning
confidence: 98%
“…In neuroimaging studies, response-level processing has been associated with age-related compensatory recruitment of neural activation (Langenecker, Nielson, & Rao, 2004;Milham et al, 2002;Nielson, Langenecker, & Garavan, 2002;Paxton, Barch, Racine, & Braver, 2008;Sebastian et al, 2013), but these previous studies have used either prepotent responses (e.g., Stroop) or relatively complex target-response mapping. Age constancy in the magnitude of the behavioral effects for response competition and inhibition has also been reported (Atwi et al, 2018;Hsieh & Lin, 2014;Kramer, Humphrey, Larish, Logan, & Strayer, 1994;Madden & Langley, 2003), and thus the specific attentional demands leading to the agerelated differences are not yet clear. To our knowledge, no previous study of age-related differences in response-level processing during visual feature search has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, microvascular insults to the brain are often assessed by white matter hyperintensities (WMH) on T 2weighted images (45)(46)(47). We therefore visually inspected the T 2 -weighted images to examine the potential presence of hyperintensities.…”
Section: Additional Anatomical Mri Sequencementioning
confidence: 99%